2015
DOI: 10.15611/pn.2015.412.25
|View full text |Cite
|
Sign up to set email alerts
|

Bezpośrednie koszty emisji akcji w pierwszej ofercie publicznej na GPW w Warszawie (Direct costs of share issuance in IPO on the Warsaw Stock Exchange)

Abstract: Informacje o naborze artykułów i zasadach recenzowania znajdują się na stronach internetowych www.pracenaukowe.ue.wroc.pl www.wydawnictwo.ue.wroc.pl Publikacja udostępniona na licencji Creative Commons Uznanie autorstwa-Użycie niekomercyjne-Bez utworów zależnych 3.0 Polska (CC BY-NC-ND 3.0 PL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Total costs were also relatively high in the year before (20.68%), and in 2009 (21.86%). The study, therefore, confirmed the conclusions of the other presented re-Pobrane z czasopisma Annales H -Oeconomia http://oeconomia.annales.umcs.pl Data: 03/04/2023 05:44:03 search (Sieradzki, 2016;Puławski, 2013;Wawryszuk-Misztal, 2015), presenting the increase in costs during the periods of crisis. The noticeable increase in costs in 2020, may be related to the emergency situation caused by the COVID-19 pandemic.…”
Section: Resultssupporting
confidence: 84%
“…Total costs were also relatively high in the year before (20.68%), and in 2009 (21.86%). The study, therefore, confirmed the conclusions of the other presented re-Pobrane z czasopisma Annales H -Oeconomia http://oeconomia.annales.umcs.pl Data: 03/04/2023 05:44:03 search (Sieradzki, 2016;Puławski, 2013;Wawryszuk-Misztal, 2015), presenting the increase in costs during the periods of crisis. The noticeable increase in costs in 2020, may be related to the emergency situation caused by the COVID-19 pandemic.…”
Section: Resultssupporting
confidence: 84%